The influence of tectonic activity on clathrate destabilisation: Microthermometry and Raman insights from seep carbonates in the Alps‐Apennines tectonic knot. (17th November 2021) - Ceriani, Andrea; Arboit, Francesco; Di Giulio, Andrea; Decarlis, Alessandro; Steuber, Thomas; Amadori, Chiara; Al Suwaidi, Aisha
Abstract: The formation of carbonate build‐ups associated with seafloor methane vents – where microbially mediated sulphate‐dependent anaerobic oxidation of methane produces alkalinity – is well documented in modern marine environments and in the geologic record. However, the triggering event(s) behind the processes leading to hydrocarbon disequilibrium, seeping and consequent deposition of seep‐carbonates remain poorly constrained. This contribution characterises the salinity, geochemistry and temperature framework of a suit of fluid inclusions from hydrocarbon‐derived seep‐carbonate veins, collected from the Marmorito Formation in the Monferrato Hills, NW Italy. The datasets yield evidence of three different precipitation events, which comprise porous structures composed of well bladed calcites and aggregated spherules of aragonite. Fluid inclusions analysis shows the presence of a heterogeneous entrapment of immiscible fluids proving the paleo‐dissolution of a suite of complex hydrocarbons, which have a wide range of closing temperature starting at ca. 60°C. These physical and chemical conditions are considered to indicate seep‐carbonate deposition driven by disequilibrium of hydrocarbon‐bearing compounds at temperatures much warmer than the background ambient bottom waters (ca. 1 to 5°C) due to the influence of the Late Oligocene to Early Miocene tectonic compression at the junction of the southern Alps and Apennines. Abstract : Micro‐thermometry and Raman analyses of fluid inclusions from seep‐carbonates. Deposition of seep‐carbonates in hydrothermal conditions over 100 °C along structural discontinuities. Link between tectonic active regions and destabilization of complex hydrocarbons.